The fundamentals of synthesis of the nanomaterials, properties, and emphasis on laser ablation in liquids: a brief review - G Krishna Podagatlapalli (Discover Nano)
Abstract Materials whose dimensions are less than 100 nm of diverse sizes and different shapes of the metal/semiconductor/insulator particles are known as nanomaterials. Nanomaterials exhibit very peculiar thermal, mechanical, electrical, optical, and chemical properties compared to their bulk counterparts. When a bulk material is chopped to a nano-dimension, electrons are subjected to peculiar boundary conditions, eventually leading to the nanomaterials' special properties. Due to their exceptional properties, nanomaterials have unique applications in all branches of science. Consequently, the researchers explored many methods of synthesis of the nanomaterials. However, each method has its advantages and disadvantages, some methods are flexible in synthesizing nanoparticles with uniform size distribution and some are feasible to produce nanomaterials at higher yields. Different methods follow their own synthesis protocols, time durations, economical feasibility, and reproducibility. Most methods complement one another by producing nanomaterials of evenly distributed sizes, shapes, properties, etc. Amongst, the, laser ablation of metals/semiconductors/insulators immersed in a liquid medium is a well-known method of green synthesis of nanomaterials that utilizes no hazardous chemical precursors. Laser ablation in liquids (LAL) combines top-down and bottom-up approaches that do not require lengthy sample preparations, chemical surfactants, and sophisticated experimental methodologies. The physical processes involved in the LAL of different metals/semiconductors are discussed briefly. Additionally, the applications of nanomaterials in various fields of science are included and the review is concluded with the challenges and the future scope of LAL.